Environmental Preservation, Uncertainty, and Irreversibility - Arrow, Kenneth J.; Fisher, Anthony C. (Quarterly Journal of Economics, 1974)
Abstract A number of recent contributions by economists have provided a clear insight into the causes of the varied forms of environmental deterioration, and have also suggested, implicitly or explicitly, policies for more efficient management of environmental as well as other resources.1 Yet, as Allen Kneese has pointed out in a review of empirical studies of pollution damages, “a general shortcoming of [these studies] has been that they have treated a stochastic or probabilistic phenomenon as being deterministic.”2 The purpose of this paper is to explore the implications of uncertainty surrounding estimates of the environmental costs of some economic activities. It is shown in particular that the existence of uncertainty will, in certain important cases, lead to a reduction in net benefits from an activity with environmental costs. In such cases the implication for an efficient control policy will generally involve some restriction of the activity.